Short Stay Management of Chest Pain - Cannon, Christopher P.; Peacock, William Franklin. (Contemporary Cardiology, 2009)
Acute coronary syndrome (ACS) continues to challenge our health care system in the complexity of presentation and the ever increasing number of patients exhibiting signs and symptoms of an acute coronary syndrome. Written by leading experts, Short Stay Management of Chest Pain provides scientific and clinical insights on the management of patients who arrive at the hospital with a presentation consistent with a potential acute coronary syndrome. Focusing on the cardiology aspects of chest pain, Short Stay Management of Chest Pain is a valuable tool for acute care physicians, nurses, and hospital administrators devoted to caring for this population. Short Stay Management of Chest Pain details the remarkable improvements in diagnostic accuracy and improved patient outcomes for patients presenting with suspected acute coronary syndromes.